2016
DOI: 10.6004/jnccn.2016.0006
|View full text |Cite
|
Sign up to set email alerts
|

Use and Effectiveness of Adjuvant Chemotherapy for Stage III Colon Cancer: A Population-Based Study

Abstract: One-third of patients with stage III colon cancer in the general population do not receive ACT. Use of ACT in routine practice is associated with a substantial improvement in CSS and OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
3
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 12 publications
3
47
3
2
Order By: Relevance
“…[1][2][3] Despite robust evidence, it is well known that not all patients will receive guideline-concordant care. Only 66% of patients in Ontario received adjuvant chemotherapy 4 ; comparable rates have been reported elsewhere. [5][6][7] Interpretation of this data is limited by the fact that the optimal utilization rate is not known.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…[1][2][3] Despite robust evidence, it is well known that not all patients will receive guideline-concordant care. Only 66% of patients in Ontario received adjuvant chemotherapy 4 ; comparable rates have been reported elsewhere. [5][6][7] Interpretation of this data is limited by the fact that the optimal utilization rate is not known.…”
Section: Introductionsupporting
confidence: 63%
“…The study population included 2801 patients with resected stage III colon cancer (Figure , Table ). Our previous analysis showed that older patients with greater comorbidity were less likely to receive ACT; surgeon/hospital volumes were not associated with ACT utilization . There were total of 72 hospitals where patients had surgery.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, there is evidence from Ontario that new forms of adjuvant treatment are used more frequently in richer communities. 20,21 Thus, it seems probable that the more rapid adoption of effective new treatments in richer communities may be responsible for the observed increase in disparity in cancer-specific survival associated with socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…[862]. In dieser retrospektiven Analyse profitierten alle Altersgruppen von einer adjuvanten Chemotherapie.…”
Section: Multiviszerale Resektionunclassified